Glycosaminoglycans in the Human Cornea: Age-Related Changes. (January 2015) - Pacella, Elena; Pacella, Fernanda; De Paolis, Giulio; Parisella, Francesca Romana; Turchetti, Paolo; Anello, Giulia; Cavallotti, Carlo
Aim: To investigate possible age-related changes in glycosaminoglycans (GAGs) in the human cornea. The substances today called GAGs were previously referred to as mucopolysaccharides. Methods: Samples of human cornea were taken from 12 younger (age 21 ± 1.2) and 12 older (age 72 ± 1.6) male subjects. Samples were weighed, homogenized, and used for biochemical and molecular analyses. All the quantitative results were statistically analyzed. Results: The human cornea appears to undergo age-related changes, as evidenced by our biochemical and molecular results. The total GAG and hyaluronic acid counts were significantly higher in the younger subjects than in the older subjects. The sulfated heavy GAGs, such as chondroitin, dermatan, keratan, and heparan sulfate, were lower in the younger subjects than in the older subjects. Discussion: GAGs of the human cornea undergo numerous age-related changes. Their quantity is significantly altered in the elderly in comparison with younger subjects. GAGs play an important role in age-related diseases of the human cornea.